The business of cultural heritage tourism: critical success factors - Hughes, Michael; Carlsen, Jack (Taylor and Francis, 2010)
This paper explores critical success factors (CSFs) required for cultural heritage tourism (CHT) operation and how these relate to commercial focus. The literature indicates tension between conservation of authenticity and commercial focus as it is seen to undermine authenticity, potentially degrading its quality and ultimate success as a tourism product. A list of nine key CHT business success factors was devised based on the published literature. Managers and operators of a range of Australian CHT operations were interviewed regarding achievement of CSFs. The operations were broadly categorised according to the level of commercial focus. The level of commercial focus was cross tabulated with the number of CHT business CSFs achieved. While all places in this study had addressed authenticity, CHT places presenting highly commercialised products tended to meet the criteria for achieving a greater number of CSFs than their less commercialised counter-parts. This has implications for sustainable CHT operation practices.